Signalling Nouns in English : A Corpus-Based Discourse Approach - Flowerdew, John; Forest, Richard W. (Cambridge : Cambridge University Press, 2015)
Signalling nouns (SNs) are abstract nouns like'fact','idea','problem' and'result', which are non-specific in their meaning when considered in isolation and specific in their meaning by reference to their linguistic context. SNs contribute to cohesion and evaluation in discourse. This work offers the first book-length study of the SN phenomenon to treat the functional and discourse features of the category as primary. Using a balanced corpus of authentic data, the book explores the lexicogrammatical and discourse features of SNs in academic journal articles, textbooks, and lectures across a range of disciplines in the natural and social sciences. The book will be essential reading for researchers and advanced students of semantics, syntax, corpus linguistics and discourse analysis, in addition to scholars and teachers in the field of English for academic purposes.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Lexical grammar